Relationship between serum transferrin saturation and catheter-related blood stream infection and prognosis in maintenance hemodialysis patients - Ding Tong; Bao Nan; Zhang Peng-jie; Du Peng; Fan Xiao-bao (Linchuang shenzangbing zazhi)
Objective To detect the serum level of transferrin saturation（TSAT）and explore the correlation between TSAT and catheter-related bloodstream infection（CRBSI）and prognosis in maintenance hemodialysis（MHD）patients.Methods A total of 183 patients with renal failure undergoing venous catheterization hemodialysis from September 2017 to September 2019 were selected as research subjects.According to the occurrence of CRBSI,they were divided into two groups of infection（n=42）and uninfected（n=141）.And 50 healthy volunteers were selected as control group.The levels of serum iron（SI）and total iron binding capacity（TIBC）were measured by Ferene method and the value of TSAT was calculated.Based upon the 30-day prognostic status, the outcomes were improvement（n=26）and extubation/death（n=16）.And the serum level of TSAT was compared between two groups.Logistic regression analysis was performed for examining the risk factors of poor prognosis.Also curve of receiver operator characteristic（ROC）was plotted for determining the diagnostic value of serum level of TSAT in MHD patients with CRBSI.Results The serum levels of SI and TSAT were significantly lower in infected group than those in control and uninfected groups（P<0.05）.And the level of TIBC was significantly higher than that in control and uninfected groups（P<0.05）.The serum levels of SI and TSAT were significantly lower in uninfected group than those in control group（P<0.05）and the level of TIBC was significantly higher than that in control group（P<0.05）.Proportion of diabetes mellitus, levels of white blood cell（WBC）and C-reactive protein（CRP）were significantly higher in poor prognosis group than those in good prognosis group（P<0.05）.And serum levels of TSAT and SI were significantly lower than those in good prognosis group（P<0.05）.Logistic regression analysis indicated that diabetes mellitus and WBC/CRP level were risk factors for poor prognosis while the level of TSAT was a protective factor.Furthermore, ROC results showed that the area under the cure（AUC）of serum level of TSAT in the diagnosis of poor prognosis was 0.853,the sensitivity 87.5% and the specificity 76.9%.Conclusion In MHD patients with CRBSI,serum level of TSAT declines markedly.As a protective factor for poor prognosis, it may be used as a potential biological index for predicting the prognosis.